2016
DOI: 10.3847/0004-637x/822/2/93
|View full text |Cite
|
Sign up to set email alerts
|

The Population of Compact Radio Sources in the Orion Nebula Cluster

Abstract: We present a deep centimeter-wavelength catalog of the Orion Nebula Cluster (ONC), based on a 30 h single-pointing observation with the Karl G. Jansky Very Large Array in its highresolution A-configuration using two 1 GHz bands centered at 4.7 GHz and 7.3 GHz. A total of 556 compact sources were detected in a map with a nominal rms noise of 3 µJy bm −1 , limited by complex source structure and the primary beam response. Compared to previous catalogs, our detections increase the sample of known compact radio so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
121
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(134 citation statements)
references
References 40 publications
13
121
0
Order By: Relevance
“…We have also recovered 64 of the 77 sources detected by Zapata et al (2004a), 9 of the 11 sources found by Zapata et al (2004b), 42 of the 54 sources found by Kounkel et al (2014), and 144 of the 556 sources found by Forbrich et al (2016). We detect 29 of the 35 sources that were previously detected at 2 cm.…”
Section: Comparison With Previous Radio Surveysmentioning
confidence: 55%
See 1 more Smart Citation
“…We have also recovered 64 of the 77 sources detected by Zapata et al (2004a), 9 of the 11 sources found by Zapata et al (2004b), 42 of the 54 sources found by Kounkel et al (2014), and 144 of the 556 sources found by Forbrich et al (2016). We detect 29 of the 35 sources that were previously detected at 2 cm.…”
Section: Comparison With Previous Radio Surveysmentioning
confidence: 55%
“…The expanded capabilities of the VLA correlator (Perley et al 2009), now enable surveys of much higher sensitivity than were previously possible. More recent surveys have taken advantage of this increase in sensitivity to map star-forming regions, including the ONC at 4.5 and 7.5 GHz (Dzib et al 2013;Kounkel et al 2014;Forbrich et al 2016). This enhanced sensitivity is well matched to the deeper observations now enabled with ALMA.…”
Section: Introductionmentioning
confidence: 60%
“…The astrometric radio studies of the Orion Trapezium-BN/ KL region appears promising for the future, since Forbrich et al (2016) detected a total of 556 compact radio sources in this region. With additional new high resolution and high sensitivity radio observations distributed in the next decade, it will be possible to measure the proper motion of these hundreds of sources and perform a comprehensive internal kinematic study of YSOs in the densest region of Orion.…”
Section: Discussionmentioning
confidence: 99%
“…5 northeast of BN. It was first reported at radio frequencies by Forbrich et al (2016) 14 with a spectral index that suggests nonthermal emission. Extrapolating the proper motions of IRc 23 to 550 years in the past it appears to agree, within the errors, with the position where sources BN, I, and n were then 14 It was, however, clearly detected before by Menten & Reid (1995) and by Gómez et al (2008).…”
Section: Fast Moving Sourcesmentioning
confidence: 99%
See 1 more Smart Citation